PREVELENCE OF SECONDARY HYPERTENSION & PRESCRIBING TRENDS IN POONCH DISTRICT (International Journal of Pharmacy & Integrated Health Sciences, 2022)
Background: Hypertension in pregnancy is one of the major causes of fetus and mother’s death. In pregnancy hypertension is of four categories preeclampsia, gestational hypertension, chronic hypertension, preeclampsia superimposed on chronic hypertension.